Diagnosing prosopagnosia in East Asian individuals: Norms for the Cambridge Face Memory Test–Chinese. Issue 5 (4th July 2017) - McKone, Elinor; Wan, Lulu; Robbins, Rachel; Crookes, Kate; Liu, Jia
ABSTRACT: The Cambridge Face Memory Test (CFMT) is widely accepted as providing a valid and reliable tool in diagnosing prosopagnosia (inability to recognize people's faces). Previously, large-sample norms have been available only for Caucasian-face versions, suitable for diagnosis in Caucasian observers. These are invalid for observers of different races due to potentially severe other-race effects. Here, we provide large-sample norms ( N  = 306) for East Asian observers on an Asian-face version (CFMT–Chinese). We also demonstrate methodological suitability of the CFMT–Chinese for prosopagnosia diagnosis (high internal reliability, approximately normal distribution, norm-score range sufficiently far above chance). Additional findings were a female advantage on mean performance, plus a difference between participants living in the East (China) or the West (international students, second-generation children of immigrants), which we suggest might reflect personality differences associated with willingness to emigrate. Finally, we demonstrate suitability of the CFMT–Chinese for individual differences studies that use correlations within the normal range.